Collateral Sensitivity of Parthenolide via NF-κB and HIF-α Inhibition and Epigenetic Changes in Drug-Resistant Cancer Cell Lines - Dawood, Mona; Ooko, Edna; Efferth, Thomas (Frontiers in Pharmacology, 2019)
Parthenolide (PT) is a sesquiterpene lactone isolated from Tanacetum parthenium. In this study, PT showed varying cytotoxic effects against different solid tumor cell lines. HCT116 (p53+/+) colon carcinoma cells and their parental HCT116 knockout p53 (p53-/-) cell lines showed a resistance degree of 2.36. On the other hand, wild-type U87.MG cells or cells transfected with a deletion-activated EGFR cDNA (U87.MGΔEGFR) exhibited slight sensitivity toward PT. Multidrug-resistant MDA-MB-231-BCRP cells were even more sensitive toward PT than sensitive MDA-MB-231-pcDNA cells with a resistance degree of 0.07 (collateral sensitivity). To the best of our knowledge, hypersensitivity (collateral sensitivity) in MDA-MB-231-BCRP cell line is reported in this study for the first time. We attempted to identify the mechanism of collateral sensitivity. Firstly, we found that PT bound to IKK preventing IκBα degradation and eventually inhibition of the nuclear factor kappa B (NF-κB) pathway. Down-regulation of hypoxia inducing factor 1-alpha (HIF-1α) in MDA-MB-231-BCRP resistant cells may be a second mechanism, since it is a target gene of NF-κB. Moreover, PT also showed epigenetic effect by inhibition of HDAC activity as shown using both molecular docking and HDAC activity assay. Based on COMPARE and hierarchical cluster analyses, we found gene expression profiles that predicted sensitivity or resistance of 47 tumor cell lines toward PT. Interestingly, pathway analyses of gene expression profiles revealed NF-κB and HIF signaling as top networks of these genes, cellular functions and canonical pathways influencing the activity of PT against tumor cells. In conclusion, PT exerted profound cytotoxic activity against various cancer cell lines mainly against BCRP-overexpressing tumor cells, suggesting PT as novel candidate for cancer treatment.